A dive into natural leads against depression from family Lamiaceae - Pargat Singh,, Ujjwal Kaushik (Journal of Applied Pharmaceutical Science, 2024)
One of the most significant herbal families, the Lamiaceae, has a vast range of plants having biological and therapeutic uses. Due to its curative and preventative qualities, species of the Lamiaceae family have a long history of usage in flavoring, food preservation, and medicine. The family comprising around 236 genera is known for the herbaceous plant species enriched in aromatic compounds. The review focuses on the potential antidepressant properties, active ingredients, and potential mechanisms of action of plant species found in the selected unexplored genus of the Lamiaceae family. The insights emphasized in this review will contribute to the body of knowledge on the unique effects of Lamiaceae plants on depression. It is possible to do more research on the plant species covered under each genus to identify and isolate potentially active substances that may have commercial application in medicinal industry.
Keywords: Depression, Lamiaceae, anxiety, antidepressant, dysthymia